2008
DOI: 10.1186/1472-6882-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito larvicidal and antimicrobial activity of protein of Solanum villosum leaves

Abstract: Background: Mosquitoes are associated with the transmission of malaria, dengue, Japanese encephalitis, filariasis and other viral diseases throughout the globe, apart from being a nuisance pest. Biological control alone or as a part of integrated vector management stands to be a better alternative to the chemical controls aimed against pest mosquitoes. At the same time it is necessary to control bacteria by synthetic or natural means (plant products). Hence the present study was designed to screen the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The phytochemical screening of plant menthol extracts showed that it contain flavonoids, terpenoids, phenols, amino acids, alkaloids and tannins, which have antimicrobial properties (Fernandez et al, 1996;Mendoza et al, 1997;Amaral et al, 1998;Cowan, 1999 ;Shaheen et al, 2003;Amarowicz et al, 2008;Chowdhury et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical screening of plant menthol extracts showed that it contain flavonoids, terpenoids, phenols, amino acids, alkaloids and tannins, which have antimicrobial properties (Fernandez et al, 1996;Mendoza et al, 1997;Amaral et al, 1998;Cowan, 1999 ;Shaheen et al, 2003;Amarowicz et al, 2008;Chowdhury et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Todate, the search for novel, potent and safer pesticides from this deposit has already provided several candidates, either as pure compounds and/or their extracts. Specifically, various organic acids such as lactic and orthophosporic acids (Chakraborty et al, 2010), alkaloids (Talontsi et al, 2011) and plant proteins (Chowdhury et al, 2008) have been identified as efficient mosquito control agents. Furthermore, several plants were used as the maternal material to produce bioproducts which were applied against mosquitoes with hopeful results (Shaalan et al, 2005;Sukumar et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…aegypti was 11.67 mg/L [18] . The bio-efficacy of Aloe vera leaf extract and bacterial insecticide, Bacillus sphaericus larvicidal activity was assessed against the first to fourth instars larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%